مقاربة ممارسات التحفظ المحاسبي في تحسين جودة القوائم المالية (أدلة من البيئة الجزائرية) - هبيته, كوكب; دمدوم, زكرياء (جامعة الوادي - University of Eloued, 2022)
هدفت هذه الدراسة إلى بيان مدى مساهمة ممارسات التحفظ المحاسبي على جودة القوائم المالية في ظل تطبيق النظام المحاسبي المالي SCF الذي تضمن مفهوم الحيطة والحذر, وقد تمت الدراسة باستخدام المنهج الوصفي التحليلي وذلك بالتطبيق على عينة من 85 تتضمن محاسبين ومسيرين لمؤسسات اقتصادية بولايات الجنوب الشرقي (الوادي، ورقلة، بسكرة) في سنة 2020، وقد تم استخدام البرنامج الإحصائيSPSS في قياس واختبار فرضيات الدراسة، تم التوصل من خلال الدراسة إلى أن هناك أثر ملموس ذو دلالة إحصائية للتحفظ المحاسبي على جودة القوائم المالية من خلال تأثيره القوي على كل من ( الإفصاح والشفافية عن المعلومات المحاسبية، جودة الأرباح المحاسبية، جودة المعلومات المحاسبية، فعالية حوكمة الشركات، تكلفة الأموال المملوكة) t: This study aimed to demonstrate the extent of the contribution of accounting conservatism practices to the quality of the financial statements in light of the application of the SCF financial accounting system, which included the concept of prudence and caution. The study was carried out using the descriptive analytical method by applying to a sample of 85 including accountants and managers of economic institutions in the southeastern states (El-oued, Ouargla, Biskra) in the year 2020. The SPSS statistical program was used to measure and test the study's hypotheses. Accordingly, the study found that there is a tangible and statistically significant impact of the accounting conservatism on the quality of the financial statements through its strong impact on each of the (disclosure and transparency of accounting information, quality of accounting profits, quality of accounting information, effectiveness of corporate governance, cost of owned funds).
Approaching accounting conservatism practices in improving the quality of financial statement
مقال
Keywords: تحفظ محاسبي ; ق ; ائم مالية ; ج ; دة معل ; مات محاسبية